Mycotic innominate artery aneurysm repair using a bovine pericardial bifurcation prosthesis. Issue 3 (11th March 2018) - Hoff, Andrea H. T.; Akca, Ferdi; Cuypers, Philippe W. M.; ter Woorst, Joost F.
Abstract: We report the use of a bovine pericardial bifurcation prosthesis to repair a mycotic innominate artery aneurysm.